Tindak tutur Ilokusi dalam Novel Finally the Netherlands - Sa’diyah, Aminatus (Maliki Interdisciplinary Journal, 2024)
This study aims to determine the forms and types of illocutionary speech acts in the novel Finally The Netherlands. In researching, the author uses a type of contextual analysis qualitative research. The data source used in this study is the storyline in the novel Finally the Netherlands which has a close connection with the academic life of students and students in the learning environment. Researchers collected data by reading and interviewing the creators of the novel directly in order to avoid mistakes and there was synchronization in the research. The method used in this research is pragmatic study. From the research results it can be concluded that in this study two conclusions were found, namely the form of illocutionary speech acts and types of illocutionary speech acts in the novel Finally The Netherlands.